2015
DOI: 10.1038/jid.2015.155
|View full text |Cite
|
Sign up to set email alerts
|

EDA Fibronectin in Keloids Create a Vicious Cycle of Fibrotic Tumor Formation

Abstract: During the early phase of wound healing, first plasma fibronectin (FN) and then in situ FN are deposited at the site of injury. In situ FN--FN made by tissue cells at the injury site--often contains an extra domain A (EDA) insert. Multiple wound-related signal transduction pathways control the deposition of EDA FN, and the EDA insert can in turn trigger pathways that induce inflammation, increased extracellular matrix molecule deposition including FN and collagen, and activation of fibroblasts. Together these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…In lung, a candidate for this effect is α4β7 integrin [27, whereas in the heart the receptor mediating this effect has not been characterized [54], although some data suggest that it might be an indirect mechanism dependent on recruitment of non-integrin toll like receptor-2-(TLR-2) expressing macrophages. The recent finding that the toll like receptor 4 (TLR-4) on inflammatory cells binds to EDA+ fibronectin in the skin has suggested this receptor to be a at the core of a co-ordinating mechanism for inflammatory and fibrotic responses in keloids [55].…”
Section: Collagen-binding Integrinsmentioning
confidence: 99%
“…In lung, a candidate for this effect is α4β7 integrin [27, whereas in the heart the receptor mediating this effect has not been characterized [54], although some data suggest that it might be an indirect mechanism dependent on recruitment of non-integrin toll like receptor-2-(TLR-2) expressing macrophages. The recent finding that the toll like receptor 4 (TLR-4) on inflammatory cells binds to EDA+ fibronectin in the skin has suggested this receptor to be a at the core of a co-ordinating mechanism for inflammatory and fibrotic responses in keloids [55].…”
Section: Collagen-binding Integrinsmentioning
confidence: 99%
“…The FN(+)EDA isoform, also known as a fetal FN, is generated by alternative splicing and is found in embryonic tissues, but not normal adult tissues (Ffrench‐Constant & Hynes, ). However, the FN(+)EDA isoform is often expressed under pathophysiological conditions, such as during cancer progression, tissue repair, and inflammation, and in association with fibrotic changes in the liver or lung (Kelsh, McKeown‐Longo, & Clark, ; Muro et al, ; Shinde et al, ). EDA‐null mice exhibit defects in wound repair (Muro et al, ) and develop atherosclerotic plaques (Pulakazhi Venu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…EDA isoform is often expressed under pathophysiological conditions, such as during cancer progression, tissue repair, and inflammation, and in association with fibrotic changes in the liver or lung (Kelsh, McKeown-Longo, & Clark, 2015;Muro et al, 2003;Shinde et al, 2015). EDA-null mice exhibit defects in wound repair (Muro et al, 2003) and develop atherosclerotic plaques (Pulakazhi Venu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, patients can have the disease without injury, normally in puberty. The pathogeny of KD remains unclear; however, previous studies have found that, as with autoimmune diseases, genetic predisposition and abnormal microenvironment contribute to KD development . Although there are many treatment options for KD, because of the lack of knowledge of the pathomechanisms underlying KD, there is currently no targeted therapy with an acceptable recovery rate, and there is a high relapse rate …”
mentioning
confidence: 99%